Advancing Gender Equality in the Workplace: Challenges, Strategies, and the Way Forward - Du, Jiaxing (Journal of Theory and Practice of Social Science, 2024)
Gender inequality remains a pervasive issue in the modern workplace, manifesting in various forms, such as wage disparities, unequal promotion opportunities, and underrepresentation in leadership roles. This paper explores the complex factors contributing to gender inequality in the workplace, including gendered organisational structures, intersectional marginalisation, and gender stereotypes and biases. Drawing upon existing literature and research, the paper discusses potential strategies for addressing these challenges, such as implementing diversity and inclusion initiatives, closing the gender pay gap, promoting work-life balance, fostering inclusive leadership, and challenging gender biases. The paper argues that achieving gender equality requires a multi-faceted approach and sustained efforts from organisations, policymakers, and society. Furthermore, promoting gender equality is a matter of fairness and justice and contributes to enhanced organisational innovation, productivity, and financial performance. The paper concludes by emphasising the need for a long-term, collaborative effort to create an inclusive workplace environment where individuals of all genders can thrive and reach their full potential.